Video Branding as AISAS Mode's Digital Marketing Strategy for Hijau Daun Mangrove Ecotourism in Bawean Island - Muhammad Arif Fadlurrahman; Luthfi Maulida Rochmah; Andreas Syah Pahlevi (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
Bawean Island is one of the islands included in the territorial area of East Java Province which has abundant natural tourism potential, one of which is Hijau Daun mangrove ecotourism. However, the community managing tourism has not been able to massively maximize digital technology to develop tourism potential by providing a complete and real picture to be able to attract tourists so that it will support the economy and welfare of the people of Bawean Island. This research aims to optimize digital-based tourism marketing through video and form a communication media group as a long arm for the sustainability of digital marketing. The method used is descriptive qualitative with data collection techniques using documentation, interviews, and questionnaires. The research subjects were the community and managers of Hijau Daun mangrove ecotourism. It is hoped that this research will be able to provide good practices for Hijau Daun mangrove ecotourism and can be applied to other potential Tourism Villages.